Ameliorative Effects of Eleutherine palmifolia Extract on Monosodium Glutamate-Induced Reproductive Toxicity: Modulation of Oxidative Stress Markers and Spermatogenesis in a Murine Model - Rahmatullah, Aldin Akbar; Ratnaningtyas, Nurrohmah; Mustofa, Imam; Mulyati, Sri; Sugihartuti, Rahmi; susilowati, Suherni; Putri, Cindy Ercha Aulia (Indonesian Andrology and Biomedical Journal, 2025)
Background : Chronic monosodium glutamate (MSG) exposure is linked to testicular toxicity, impacting spermatogenesis and oxidative stress markers. Objective : This study investigated the protective effects of Dayak onion (Eleutherine palmifolia) extract against MSG-induced testicular damage in mice. Methods : Twenty-five male mice (11 weeks, ~20 g) were divided into five groups: negative control (C-, 0.5% CMC-Na), positive control (C+, MSG 4 mg/g BW), and treatment groups (T1, T2, T3) receiving MSG plus Dayak onion extract (30, 60, 120 mg/kg BW, respectively) for 52 days. On day 53, testicular histology and serum malondialdehyde (MDA) and superoxide dismutase (SOD) levels were analyzed. One-way ANOVA and Duncan’s post hoc test assessed differences (p<0.05). Results : Group C+ showed significantly reduced spermatogenic cell counts, elevated MDA, and decreased SOD compared to C-. Group T1 exhibited no significant improvement in spermatogonia and spermatocytes but increased spermatids. Groups T2 and T3 significantly improved spermatogenic cell counts, with T3 showing the closest recovery to C-. MDA levels decreased, and SOD activity increased dose-dependently, with T3 nearing C- levels. Conclusion : Dayak onion extract, particularly at 120 mg/kg BW, mitigates MSG-induced testicular toxicity, preserving spermatogenesis and balancing oxidative stress markers.